Assessment of Pump’s Performance in Water Supply Systems – Data Collected from Multiple Case Studies - Cardoso, Pedro; Santos, António; Rato, Ricardo; Estrela, Marco (European Journal of Sustainable Development, 2017)
This paper reports the evaluation of pump’s efficiencies and its optimization potential, in three water supply systems. The study surveyed 65 pumps groups, from 24 pumping stations, between 5 to 350 kW of absorbed power, with flow rates from 25 to 1500 m3/h. The performance of the pumps, was assessed by testing each pump group in different operational conditions. It was quantified, for each pump group, the specific consumption (kWh/m3) and cost (€/m3) as well as the difference between the optimum efficiency point, for the specific net head of each installation, and their actual operating point. The identified energy inefficiencies and proposed corrective measures for each pump group were compiled in order to improve their efficiency. Most problems identified are oversized groups, valve problems and inadequate operational working points. On average the surveyed pump’s efficiencies were 10 percentage points below their reference values. In order to reduce the gap several improvement measures were proposed, such as the refurbishment of the pumps, impeller adjustments, variable speed drive installation and the extension of the working periods with lower frequency regimes, where high efficiencies were identified. The implementation of these improvement measures has an energy saving potential of 331 MWh/year, which means 27.000 €/year.